PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Taufan Ardiyanto; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
This study aims to empirically examine the relationship disclosure behaviour of Corporate Social Responsiblty to the company perfromance and its implication for company value in Indonesian Listed Companies. In this study, the dependent variable is firm value which is proxied by Tobin’s q. Intervening variable is financial performance measured by Return on Equity (ROE), Return on Assets (ROA). The population in this study are manufacturing companies listed on the Indonesian Stock Exchange (IDX) period between 2013 to 2015 which determined by purposie sampling method. Data analysis techniques performed by regression analysis